Inside, outside, before or after? – The space-time politics of Notícias da América, by Paulo Nazareth (PerCursos, 2021)
This article investigates the performance Notícias da América, by the artist Paulo Nazareth. It identifies discussions (and actions) that handle a plurality of pasts (ancestral, colonial) and, at the same time, open relational perspectives a-typical feature of contemporary art since the 1960s. In that performance, as Nazareth moves through Latin American cities, the images and discourses produced forge a common space between himself, his interlocutors and the landscape. Simultaneously, a multiple temporality emerges in which peripheral subjectivities become visible. It is also from this space-time relationship that other of his artistic productions (such as the series Aqui é arte) can be unfolded.
Keywords: latin-american art; performance; Paulo Nazareth; hybrid temporalities; post-utopian